Association between love breakup and suicidal ideation in Peruvian medical students: a cross-sectional study during the COVID-19 pandemic - Valladares-Garrido, Danai; Zila-Velasque, J. Pierre; Santander-Hernández, Flor M.; Guevara-Morales, Miguel A.; Morocho-Alburqueque, Noelia; Failoc-Rojas, Virgilio E.; Pereira-Victorio, César Johan; Vera-Ponce, Víctor J.; León-Figueroa, Darwin A.; Valladares-Garrido, Mario J. (Frontiers in Psychiatry, 2024)
Objective: We aimed to determine the association between a major romantic breakup and suicidal ideation in medical students from three universities in Peru. Methods: A cross-sectional study was conducted during the first pandemic wave in 2021 on medical students from three universities in northern Peru. The outcome was suicidal ideation, measured with question nine of the Patient Health Questionnaire-9 (PHQ-9). Generalized Anxiety Disorder Scale-7 (GAD-7) and Insomnia Severity Index (ISI) were also used to assess mental health symptoms. The exposure was the experience of a major love breakup during the pandemic. In addition, its association with other covariates (age, sex, family members infected with COVID-19, deceased family members with COVID-19, insomnia, and anxiety, among others) was examined. Results and discussions: Out of 370 students, 19.5% reported a major love breakup during the pandemic (95%CI: 15.5–23.8), and 34.3% had suicidal ideation (95%CI: 29.4–39.4). Having a major love breakup was associated with a higher prevalence of suicidal ideation (PR: 1.49, 95%CI: 1.32–1.67,p<0.001). Moderate insomnia (PR: 2.56, 95%CI: 1.70–3.87, p<0.001) and anxiety symptoms (PR: 1.94, 1.10–3.44, p=0.023) were also associated with suicidal ideation. Conclusion: Our study provides evidence of a significant association between a major love breakup and suicidal ideation. This finding emphasizes the need for further research to better understand this association and inform the development of effective suicide prevention policies in medical education.